2012
DOI: 10.1111/j.1469-0691.2011.03517.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of Raman spectroscopy in the epidemiology of methicillin-resistant Staphylococcus aureus of human- and animal-related clonal lineages

Abstract: In order to perform a cost-effective search and destroy policy for methicillin-resistant Staphylococcus aureus (MRSA), a quick and reliable typing method is essential. In an area with a high level of animal-related MRSA ST398, pulsed field gel electrophoresis (PFGE) typing and spa-typing are not sufficient to discriminate between co-incidental findings and true transmission of MRSA. This study is the first to retrospectively show the performance of Raman spectroscopy in 16 well-documented outbreaks. We analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Our findings are comparable to those of a study performed by Wulf et al (14). In this study, the observed concordance between SCRA and the gold standard of PFGE was 97%, whereas in our study the observed concordance between SCRA and PFGE was 95%.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are comparable to those of a study performed by Wulf et al (14). In this study, the observed concordance between SCRA and the gold standard of PFGE was 97%, whereas in our study the observed concordance between SCRA and PFGE was 95%.…”
Section: Discussionsupporting
confidence: 89%
“…We hypothesized that Raman spectroscopy possibly could be used for this type of analysis. In recent years several researchers showed a high discriminative power in the field of identifying bacteria but also in several forms of cancer in which Raman spectroscopy showed to be able to diagnose prostate and bladder cancer in vitro , premalignant lesions on cervical cancer, and diagnosis of skin cancer …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, spectral shifts also occurred when ampicillin resistance was activated [28]. Raman spectroscopy has been successfully employed for the investigation of epidemic outbreaks of infections in hospitals, including the analysis of heterogeneity in isolated clones [2931]. Raman-based characterization has been used in addition to common methods such as serotyping, pulse field gel electrophoreses and genotyping using amplified fragment length polymorphism or 16S RNA sequencing to characterize microorganisms on a subclonal level [18, 19, 30, 32].…”
Section: Raman Spectroscopy and Its Application In Microbiology Andmentioning
confidence: 99%